PELATIHAN PENGGUNAAN MICROSOFT POWER POINT UNTUK MEMBUAT SLIDE ANIMASI BAGI PARA GURU SDN MERUYA UTARA 05 PAGI - Salamah , Umniy; Jumaryadi, Yuwan; Priambodo, Bagus (Universitas Nusantara PGRI Kediri, 2022)
Microsoft PowerPoint is a computer program for presentations developed by Microsoft in the Microsoft Office package. Microsoft PowerPoint is very widely used by offices and business people, educators, students, and trainers. However, there are also several schools that have teaching staff who have not mastered Microsoft Office. One of the elementary schools in Jakarta whose teachers are not yet proficient in Microsoft Office is Public Elementary School 05 Meruya Utara, especially Microsoft Power Point. So that Community Service is being held this time, namely Training on Making Animation Slides Using Microsoft Power Point for Teachers of SDN Meruya Utara 05 Pagi. The purpose of holding the community service this time is that Participants are introduced to the basics of Microsoft Power Point then make simple animations. Introducing how to operate Microsoft Power Point easily and understandably. Participants who have attended the training are expected to be able to pass on the knowledge they have gained in the training to their colleagues. The application used is Microsoft Power Point 2010. This community service was held at Meruya Utara 05 Public Elementary School, West Jakarta.